CHANGES AND CONTINUITY OF SELECTED TRADITIONAL HEALTHCARE PRACTICES IN IZZI SINCE 1905 - Mbam, Ndubuisi M. (EBSU Journal of Social Sciences and Humanities, 2024)
This academic exercise interrogates the changes and continuity in traditional healthcare practices in Izzi from 1905 to 2013. It examines the traditional healthcare practices that were utilized to cure diseases in Izzi within the above stated period. This study x-rays the healthcare practices of the people with the aim of bringing to limelight those aspects of their traditional healthcare practices that changed or were sustained over time; taking note of the factors responsible viz a viz colonialism, western education and Christianity in the region and how Western medicine contributed in shaping the healthcare landscape of Izzi. This academic enquiry discovers that for some reasons, the study of traditional healthcare practices of the Izzi has not received conscious scholarly attention hence, this thesis perhaps would create academic awareness which would elicit further studies on this aspect of the people’s History. The nature of this research necessitated the use of primary and secondary source materials which includes; archival sources, oral interviews obtained from versed individuals in the field, newspaper reports, books, journals and internet materials which were analyzed and utilized for the development of this research. This study unveils the evolution and union of traditional cum western healthcare practices in the region in question. Findings reveal both transformative shifts and enduring elements in Izzi's traditional healthcare practices. The implications of these changes extend to public health, cultural preservation, and historical understanding. This research contributes to the broader discourse on the intersection of healthcare, culture, tradition, history and would be useful to community health workers, scholars, researchers and the general public.